Pengaruh Pertumbuhan Sektoral Terhadap Pengangguran di Indonesia - Shania Delicia; Muhammad Irfan (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the impact of growth in the agriculture, mining and quarrying, manufacturing, trade, and services sectors on the open unemployment rate across Indonesia's 34 provinces from 2015 to 2024, while controlling for population growth, average years of schooling, life expectancy, gross fixed capital formation, and the poverty rate. Secondary panel data from Statistics Indonesia (BPS) were analyzed using the Feasible Generalized Least Squares (FGLS) method. The findings reveal that growth in the agriculture sector has a negative but statistically insignificant effect on the open unemployment rate. Conversely, growth in the mining and quarrying, manufacturing, trade, and services sectors exerts a negative and significant influence on the open unemployment rate in Indonesia. Among the control variables, average years of schooling, life expectancy, and gross fixed capital formation were found to have significant effects, whereas population growth and the poverty rate did not. These estimation results indicate that efforts to reduce the open unemployment rate in Indonesia require policies that strengthen the growth of economic sectors with high labor-absorption potential, supported by improvements in the quality of human resources.